KEKUATAN CINTA YANG TERCERMIN DALAM CERITA PENDEK â€œBROKEBACK MOUNTAINâ€DAN â€œA TYPE OFLOVE STORYâ€ - WATTIMENA, FIKI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Â The skripsi, entitled â€œKekuatan Cinta yang Tercermin dalam Cerita Pendek â€œBrokeback Mountainâ€ dan â€œA Type of Love Storyâ€â€, aims at identifying and analyzing the power of love reflected through the main character. The data were collected by focusing on the characters, setting and plot as the elements of prose which reveal the power of love in the short stories â€œBrokeback Mountainâ€ and â€œA Type of Love Storyâ€. In analyzing the character, the writer used the theory of Roberts concerning the character as the representation of human being. The writer also used Stenbergâ€™s idea to identify the power of love in the whole sequence of the story. The findings of this research show that these two literary works reflect the power of love portrayed by the intrinsic elements such as character, setting, and plot of the short stories. Both of these short stories have similarities and differences in terms of the power of love. The similarities lie first, in the beginning of love that starts from mere lust; second, at the end of love that ends in failure; and third, in the hidden love relation of the characters. The differences lie in the characters, perspectives of love and in the type of love they experience. Â Â Keywords: Short Stories, Brokeback Mountain, A Type of Love Story, Characters, Power of Love